Training changes processing of speech cues in older adults with hearing loss - Anderson, Samira; White-Schwoch, Travis; Choi, Hee Jae; Kraus, Nina (Frontiers in Systems Neuroscience, 2013)
Aging results in a loss of sensory function, and the effects of hearing impairment can be especially devastating due to reduced communication ability. Older adults with hearing loss report that speech, especially in noisy backgrounds, is uncomfortably loud yet unclear. Hearing loss results in an unbalanced neural representation of speech: the slowly-varying envelope is enhanced, dominating representation in the auditory pathway and perceptual salience at the cost of the rapidly-varying fine structure. We hypothesized that older adults with hearing loss can be trained to compensate for these changes in central auditory processing through directed attention to behaviorally-relevant speech sounds. To that end, we evaluated the effects of auditory-cognitive training in older adults (ages 55-79) with normal hearing and hearing loss. After training, the auditory training group with hearing loss experienced a reduction in the neural representation of the speech envelope presented in noise, approaching levels observed in normal hearing older adults. No changes were noted in the control group. Importantly, changes in speech processing were accompanied by improvements in speech perception. Thus, central processing deficits associated with hearing loss may be partially remediated with training, resulting in real-life benefits for everyday communication.